Reusable electrospun carbon nanofiber composite for selective removal of inorganic arsenic species in water. Issue 1 (1st January 2021) - Wei, Xiaoyang; Guo, Qi; Li, Yuan; Zheng, Liwei; Li, Zhiqiong; Zhang, Ke-Gang; Yuan, Chun-Gang
ABSTRACT: It is very important to develop effective and reusable functional materials for arsenic removal from water. In this study, one carbon fiber nanocomposite mat modified with ceria oxide nanoparticles was successfully prepared by electrospinning. The adsorption performances of the composite for different arsenic species were systematically investigated. The composite possessed good performance for selective adsorption of As Ⅴ at pH 12 without obvious coexisting ion interference effects. The adsorption processes fitted well with the quasi-first-order dynamics and Langmuir isotherm models. The composite mat is stable and reusable, and can be easily isolated from water after use. The prepared composites were characterized by scanning electron microscope and energy-dispersive spectroscope (SEM-EDS), x-ray diffraction spectrometry (XRD) and Fourier transform infrared spectrum (FTIR), and the possible adsorption mechanism was also discussed.